Simulation modeling of the tracking electric drive of sorting conveyor - S. N. Kladiev; A. D. Umurzakova; N. D. Sarbasova; K. V. Khatsevskiy (Омский научный вестник)
The aim of the study is to develop methods for forming a control channel for sorting roundwood based on an asynchronous three-phase motor with a phase rotor. In the study, a simulation modeling method is used to verify the operability of the developed implementation of the control channel, and to evaluate the errors in the functioning of the control system. Based on the results obtained, it can be concluded that the proposed method of forming a control channel for controlling discrete sorting devices can be used.